EDUKASI TENTANG PEMBERIAN ASI EKSKLUSIF PADA WANITA HAMIL TRIMESTER III DI PUSKESMAS BASARANG KABUPATEN KAPUAS - Bella Bella; Nita Kusuma Lindarsih; Ivana Devitasari; Yulanda Esteriani (MAJU : Indonesian Journal of Community Empowerment, 2026)
Exclusive breastfeeding is a crucial measure for improving maternal and infant health; however, pregnant women's knowledge regarding the benefits and practices of breastfeeding still requires improvement. This community service activity aimed to enhance the knowledge of third-trimester pregnant women regarding exclusive breastfeeding at the Basarang Community Health Center (Puskesmas), Kapuas Regency. The method employed involved health education—delivered through interactive lectures, discussions, Q&A sessions, and the distribution of leaflets—to 15 third-trimester pregnant women. Evaluation was conducted using pre-tests and post-tests. The results showed an increase in the average knowledge score from 62.0 to 88.7 following the education. The proportion of participants with a "good" level of knowledge rose from 20.0% to 86.7%, while the percentage with "poor" knowledge fell to 0%. The education proved effective in increasing the knowledge and readiness of pregnant women regarding exclusive breastfeeding. Similar activities should be implemented sustainably through antenatal care services to support increased exclusive breastfeeding coverage.